Hiv og aids i Russland: regimedynamikk og respons - Udal, Julie Helseth (Nordisk Østforum, 2019)
Abstract: HIV and AIDS in Russia: Regime Dynamics and Response Over the last two decades, the number of persons living with HIV in Russia has increased dramatically. According to WHO criteria, Russia is now facing a generalized HIV epidemic. This article analyzes how regime dynamics have influenced Russia’s capacity to build a domestic response to the epidemic. Putin’s cultural conservative turn in 2012 may have negatively affected the regime’s ability to curb the spread of HIV. Evidence collected for this study indicates that three developments in particular have contributed to this. The first is the introduction of legislation aimed at reducing foreign involvement in Russia, which has weakened civil society as the main provider of prevention programs and services to key populations, and has forced global agencies to leave the country. Secondly, the increasing use of value-based conservative rhetoric after 2012 has meant better access to state structures, policy crafting and governmental funding for actors opposed to conventional methods of preventing HIV. Lastly, Putin’s post-2012 cultural conception of the state has served to entrench Russian neopatrimonialism. As neopatrimonialism creates conditions unfavorable to successful implementation of reforms, including those necessary to deal with the ongoing epidemic, its stabilization may have assisted inaction as regards HIV.